KOLABORASI EDU-KREATIF: MEMBENTUK KARAKTER ANAK SEHAT, AKTIF, DAN CERIA MELALUI PEMBIASAAN PHBS SEJAK DINI DI TK KB GRIYA PERMATA - Selli Dosriani Sitopu; Magdalena Ginting; Rosita Saragih; Poniyah Simanullang; Hetti Marlina Pakpahan; Zulkarnain Nasution (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2026)
Early childhood health problems in suburban areas like Tanjung Anom, Deli Serdang Regency, bordering Medan, are still dominated by infectious diseases such as diarrhea and URI due to the lack of Clean and Healthy Living Behavior (CHLB/PHBS) habituation. At TK KB Permata Jaya, this issue is compounded by teachers' limitations in designing interactive health education media, resulting in low student PHBS practice. This community service aims to build healthy, active, and cheerful child characters through an "Edu-Creative Collaboration" approach. The implementation method involved a synergy between lecturers, teachers, and students through three stages: creative media workshops for teachers, education based on storytelling and song arrangements for students, and assistance in Handwashing with Soap (HWWS) practice. The results showed an 85% increase in teacher competence in designing PHBS monitoring instruments and a significant positive behavior change in students, where 90% of students are now accustomed to practicing HWWS independently after playing. This participatory collaboration is proven effective in laying the foundation for children's healthy character from an early age.